Exploring the top 30 drugs associated with drug-induced thrombotic microangiopathy based on the FDA adverse event reporting system - Yin, Yi; Meng, Fanmin; Fan, Yanjiao (Frontiers in Pharmacology, 2025)
BackgroundDrug-induced thrombotic microangiopathy (TMA) significantly impacts patient health and quality of life. This study aims to conduct an exploratory analysis of TMA reports and the most frequently associated drugs in the FDA Adverse Event Reporting System (FAERS) database.MethodsWe analyzed FAERS reports associated with TMA from the first quarter of 2004 to the fourth quarter of 2024. A disproportionality analysis was conducted to detect significant safety signals. Potential causative drugs were identified, and the top 30 medications with the highest number of TMA reports and strongest signal strengths were ranked accordingly.ResultsAnalysis of 22,375,298 reports in the FAERS database identified 13,748 cases of thrombotic microangiopathy (TMA). Among the top 30 medications potentially associated with drug-induced TMA, antineoplastic and immunomodulatory agents predominated both in reporting frequency and signal strength metrics. Disproportionality analysis specifically revealed multiple drugs not currently labeled for TMA risk, with antineoplastic agents comprising the majority. Notably, several less frequently implicated agents - including micafungin, foscarnet, ketoprofen, and atovaquone - also demonstrated significant associations. These pharmacovigilance signals require cautious interpretation given the inherent limitations in establishing definitive causality through spontaneous reporting data.ConclusionOur comprehensive analysis of drug rankings and signal strengths associated with TMA in FAERS underscores the critical role of pharmacovigilance in identifying and understanding drug-induced TMA. These findings necessitate further research to validate the observed associations and to develop effective risk management strategies, ultimately improving patient outcomes. This study provides valuable evidence to support the accurate clinical identification of drug-related TMA.